PRIMARY TASK OF EFFICIENT MANAGEMENT BEHAVIOUR SUBJECT ON MARKET OF PREMISES - R. M. Dullueva; M. N. Isalova (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
In work are considered main problems of the shaping the model principle to organizations of behavior management different subject on the market of the premises. It is offered use linguistically variable for generalized presentations different segment market and buildings information-analytical model of the taking the efficient management decisions.